Study of the in vitro Anti-bacterial Susceptibility of the Commercially Available Antibiotics in Suspension or Solution Forms Collected within Dhaka Metropolis - Bhuiyan, Asma Akter; Niloy, Mehran Mosharraff Hossain; Chakrabarty, Anamika; Maniha, Syeda Muntaka; Noor, Rashed (Bangladesh Journal of Microbiology, 2020)
Consumption of a range of antibiotics upon bacterial infections is a common chemotherapeutic practice. Current study attempted to detect the in vitro anti-bacterial activities of such finished medicaments against some of the selected bacterial strains in order to examine their sustainable effectiveness against microorganisms. A total of six categories of samples were randomly collected from different pharmacies within the city of Dhaka. The antibacterial susceptibility tests were conducted employing the Kirby-Bauer (agar well diffusion) method. The test bacterial strains used in this study were Escherichia coli, Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa and P. putida and P. fluorescence. While E. coli was found to be sensitive towards all the antibiotics used, others showed resistance to a significant extent. flucloxacillin, cephradine and salbutamol were noticed to be completely inactive against Pseudomonas species. Besides, the salbutamol was found only to suppress the growth of E. coli but the other five test organisms were completely resistant against this antibiotic solution. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 79-83